8 mile - Grazer, Brian, 1953-; Hanson, Curtis; Iovine, Jimmy; Silver, Scott; Eminem (Musician); Basinger, Kim, 1953-; Murphy, Brittany; Phifer, Mekhi, 1975-; Jones, Evon.; Miller, Omar Benson; Prieto, Rodrigo; Rabinowitz, Jay.; et al. (Universal City, CA : Universal, 2003)
Jimmy, known to his friends as Rabbit, is a young man trying to make his way out of the burned-out shell of inner-city Detroit. Rabbit is a white kid trying to make music in a predominantly African-American community and culture. After Rabbit freezes up in the midst of an MC battle, he's convinced he's missed his chance and that he's doomed to lead a marginal life as a factory rat for the rest of his days. With the help of his friends, and his new girlfriend Alex, Rabbit struggles to work up the courage and the confidence to take one more shot at making his dream a reality.
Originally produced as a motion picture in 2002.
Special features: exclusive never-before-seen rap battles with Eminem; exclusive never-before-seen music video (from The Eminem Show album); Eminem talks about making "8 mile"; authentic "8 mile" with Curtis Hanson; the music of "8 mile."
Director of photography, Rodrigo Prieto ; editors, Jay Rabinowitz, Craig Kitson ; original music, Eminem ; costume designer, Mark Bridges ; production designer, Philip Messina.
Eminem, Kim Basinger, Brittany Murphy, Mekhi Phifer, Evan Jones, Omar Benson Miller.
MPAA rating: R; for strong language, sexuality, some violence and drug use.
Also issued on VHS.
Keywords: Rap (Music) -- Drama; Rap musicians -- Michigan -- Detroit -- Drama; Man-woman relationships -- Drama; Friendship -- Drama; Feature films; Video recordings for the hearing impaired